2011
DOI: 10.1186/1471-2180-11-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes differentially expressed during interaction of Mexican lime tree infected with "Candidatus Phytoplasma aurantifolia"

Abstract: Background"Candidatus Phytoplasma aurantifolia", is the causative agent of witches' broom disease in Mexican lime trees (Citrus aurantifolia L.), and is responsible for major losses of Mexican lime trees in Southern Iran and Oman. The pathogen is strictly biotrophic, and thus is completely dependent on living host cells for its survival. The molecular basis of compatibility and disease development in this system is poorly understood. Therefore, we have applied a cDNA- amplified fragment length polymorphism (AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
135
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(143 citation statements)
references
References 37 publications
8
135
0
Order By: Relevance
“…The LuxI-type proteins synthesize various AHL signals, and LuxR-type transcriptional regulatory proteins bind their cognate signal and in turn induce/repress multiple gene expression accordingly [27]. However, lux I and lux R genes do not occur in pairs in the YD25 T genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LuxI-type proteins synthesize various AHL signals, and LuxR-type transcriptional regulatory proteins bind their cognate signal and in turn induce/repress multiple gene expression accordingly [27]. However, lux I and lux R genes do not occur in pairs in the YD25 T genome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a wide spectrum of important processes, such as bioluminescence, motility, sporulation, virulence, and biofilm formation, are also regulated by the QS system, which influences bacteria community gene regulation by cell–cell communication via the production and detection of diffusible auto-inducer signaling molecules [27]. Generally, the most extensively described QS system in Gram-negative bacteria is the autoinducer-1 (AI-1)-mediated system, which employs N-acyl-L-homoserine lactone (AHL) as the autoinducer signaling molecules [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies of the PAIs in virulent E. faecalis strains revealed substantial cross-strain variations in PAI gene content, even within a clonal lineage, suggesting that different segments of the island can vary independently15. Identification of novel gene modules in virulent strain type ST6 that were previously not thought to be associated with the E. faecalis PAI also pointed towards the dynamic character of the island16. It has been reported that the modular integrity of PAIs does not correlate with the evolutionary relatedness of the respective strains as determined by MLST analysis1011 and a clear idea about the genesis of PAI is yet to be emerged.…”
mentioning
confidence: 94%
“…The genomics study indicated a number of genes that might be involved in the interaction of Mexican lime trees with "Ca. P. aurantifolia" Zamharir et al, 2011). Ehya et al (2013) detected miRNA families that are expressed differently upon infection with phytoplasma species.…”
Section: Introductionmentioning
confidence: 99%